2020
DOI: 10.3390/d12040148
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence Drives Invasibility of Plant Communities at the Edges of a Resource Availability Gradient

Abstract: Invasive Alien Species (IAS) are a serious threat to biodiversity, severely affecting natural habitats and species assemblages. However, no consistent empirical evidence emerged on which functional traits or trait combination may foster community invasibility. Novel insights on the functional features promoting community invasibility may arise from the use of mechanistic traits, like those associated with drought resistance, which have been seldom included in trait-based studies.Here, we tested for the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 90 publications
(118 reference statements)
1
15
0
Order By: Relevance
“…The differences we observed in IAS distribution across habitats might be indirectly inferred by considering both habitat features and IAS functional traits and referring to IAS autoecology described in other studies [13,19,41,89]. Analyzing one habitat at a time and both the IAS frequencies and abundances that were significantly higher (or lower) than expected by chance, starting from the aquatic vegetation, we observed that the only successful invader here was Elodea nuttallii, a perennial submerged rooted hydrophyte native to North America.…”
Section: Discussionsupporting
confidence: 61%
“…The differences we observed in IAS distribution across habitats might be indirectly inferred by considering both habitat features and IAS functional traits and referring to IAS autoecology described in other studies [13,19,41,89]. Analyzing one habitat at a time and both the IAS frequencies and abundances that were significantly higher (or lower) than expected by chance, starting from the aquatic vegetation, we observed that the only successful invader here was Elodea nuttallii, a perennial submerged rooted hydrophyte native to North America.…”
Section: Discussionsupporting
confidence: 61%
“…The capacity of IAS to modulate functional traits in response to environmental changes is particularly useful in environments such as Mediterranean ones, characterized by seasonal resource fluctuations, as they allow IAS either to successfully exploit the resource surplus under high availability conditions or to use resources more efficiently in limiting conditions [ 27 , 28 , 29 , 30 ]. At a physiological level, studies on IAS capacity for acquiring resources showed that their competitive advantage is usually associated with a higher CO 2 assimilation rate [ 31 , 32 , 33 ] and is supported by an increased photosynthetic pigment and carbohydrate content [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive alien species (IAS) are recognized as an important threat to biodiversity worldwide [22] and especially in rare and extreme environments (such as alpine zone or isolated islands, [23][24][25]). On dune ecosystems, in particular, IAS alter the structure of native communities in different ways: reducing functional, phylogenetic and taxonomic diversities and excluding closely related and ecologically similar taxa [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%